Fatigue and fracture behaviour of laser powder bed fusion stainless steel 316L : influence of processing parameters - Zhang, Meng (2020)
The laser powder bed fusion (L-PBF) process involves a large number of processing parameters. Extending the intricate relationship between processing and structure to mechanical performance is essential for structural L-PBF materials. The high cycle fatigue properties of L-PBF parts are very sensitive to process-induced porosities which promote premature failure through the crack initiation mechanisms. Results from this work show that for stainless steel 316L, porosity does not impinge on the high cycle fatigue properties when processing is kept within a ±30% tolerance band. In this ‘optimum’ processing region, crack initiation takes place due to defects at the solidification microstructure level. Beyond the ‘optimum’ processing region, over-melting and under-melting can lead to porosity-driven cracking and inferior fatigue resistance. In addition, regardless of the processing condition, fatigue resistance was found to follow a direct linear relationship with ductility and tensile strength in the low and high stress fatigue regimes respectively.